TW68, cryptochromes stabilizer, regulates fasting blood glucose levels in diabetic ob/ob and high fat-diet-induced obese mice - Surme, Saliha; Ergun, Cagla; Gul, Seref; Akyel, Yasemin Kubra; Gul, Zeynep Melis; Ozcan, Onur; Ipek, Ozgecan Savlug (Pergamon-Elsevier Science Ltd, 2023)
Cryptochromes (CRYs), transcriptional repressors of the circadian clock in mammals, inhibit cAMP production when glucagon activates G-protein coupled receptors. Therefore, molecules that modulate CRYs have the po-tential to regulate gluconeogenesis. In this study, we discovered a new molecule called TW68 that interacts with the primary pockets of mammalian CRY1/2, leading to reduced ubiquitination levels and increased stability. In cell-based circadian rhythm assays using U2OS Bmal1-dLuc cells, TW68 extended the period length of the circadian rhythm. Additionally, TW68 decreased the transcriptional levels of two genes, Phosphoenolpyruvate carboxykinase 1 (PCK1) and Glucose-6-phosphatase (G6PC), which play crucial roles in glucose biosynthesis during glucagon-induced gluconeogenesis in HepG2 cells. Oral administration of TW68 in mice showed good tolerance, a good pharmacokinetic profile, and remarkable bioavailability. Finally, when administered to fasting diabetic animals from ob/ob and HFD-fed obese mice, TW68 reduced blood glucose levels by enhancing CRY stabilization and subsequently decreasing the transcriptional levels of Pck1 and G6pc. These findings collectively demonstrate the antidiabetic efficacy of TW68 in vivo, suggesting its therapeutic potential for controlling fasting glucose levels in the treatment of type 2 diabetes mellitus.
Keywords: Cryptochrome; Circadian rhythm; Type 2 diabetes; Small molecule; Drug discovery; Pharmacokinetic; Pharmacodynamic; Toxicity